2022
DOI: 10.1186/s10194-022-01481-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional improvement in children and adolescents with primary headache after an interdisciplinary multimodal therapy program: the DreKiP study

Abstract: Background More than 2/3 of children and adolescents in Germany regularly suffer from headaches. Headache-related limitations in everyday life, school drop-out and educational impairment are common. Structured therapy programs for young headache patients are widely missing. Methods One hundred eleven patients with frequent migraine and/or tension type headache were treated in a 15 hour group program in afternoons, parallel with school, parents rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
3
0
5
Order By: Relevance
“…In the present study, NLP intervention significantly decreased headaches, stomachaches, and other sickness. An earlier study in Germany revealed an improvement in the daily function of migraine patients after receiving an interdisciplinary outpatient therapy program [20] . While medical treatments like medications and procedures are often essential, non-medical interventions can complement these approaches and contribute to a holistic pain management strategy [21] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NLP intervention significantly decreased headaches, stomachaches, and other sickness. An earlier study in Germany revealed an improvement in the daily function of migraine patients after receiving an interdisciplinary outpatient therapy program [20] . While medical treatments like medications and procedures are often essential, non-medical interventions can complement these approaches and contribute to a holistic pain management strategy [21] .…”
Section: Discussionmentioning
confidence: 99%
“…140 Kinder und Jugendliche nahmen von Januar 2018 bis Juni 2022 am interdisziplinären multimodalen ambulanten Therapieprogramm DreKiP (Dresdner Kinder- und Jugendkopfschmerzprogramm) teil. Ein Teil der hier auf geschlechterspezifische Therapieantwort untersuchten Kohorte wurde bereits in der Gesamtheit ausgewertet und publiziert [ 22 ]. Die Therapiegruppen wurden nach dem Alter gebildet (9- bis 10-Jährige, 11- bis 13-Jährige, 14- bis 16-Jährige, 17- bis 19-Jährige).…”
Section: Methodenunclassified
“…DreKiP besteht aus 8 Therapiemodulen für Patienten, darunter Kopfschmerzaufklärung, Stressbewältigung, Entspannungstechniken, körperliche Fitness, Klettertherapie als Selbstwirksamkeitstraining, Kunsttherapie, Riechtraining als Edukation zum Einfluss von Sinnesreizen und Achtsamkeitstraining [siehe [ 22 , 23 ]]. Elternworkshops mit dem Schwerpunkt Edukation finden an 4 Terminen parallel statt.…”
Section: Methodenunclassified
See 1 more Smart Citation
“…These techniques have demonstrated efficacy in the treatment of pediatric headache [ 78 ] and are well accepted by patients and parents because of the very low risk of adverse effects in comparison with pharmacological treatments [ 79 ]. A recent interdisciplinary multimodal therapy program (which involved eight modules regarding headache education, stress management, relaxation techniques, physical activation, mindfulness and sensory training) showed reduced headache frequency and disability at six and twelve months after completion [ 80 ]. The best-known behavioral treatments for TTH are electromyographic (EMG) biofeedback and thermal biofeedback [ 81 , 82 ], which have shown greater responses in children than in adults [ 77 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%